Stevenia deceptoria (Diptera, Rhinophoridae): Chile’s second woodlice-parasitizing fly species studied using citizen science - Barahona-Segovia, Rodrigo M.; Mulieri, Pablo R.; Pañinao-Monsálvez, Laura (Journal of Asia-Pacific entomology, 2024)
[Display omitted] Stevenia deceptoria is a woodlouse-parasitizing fly species that has recently been introduced into South America and was until now known only in Argentina. In those countries it has invaded, this exotic fly prospers in cities because of the abundance of potential hosts in gardens and public parks. Here we show that S. deceptoria has been detected in urban ecosystems in the Metropolitan and Valparaíso Regions using citizen science and we describe its current range in the city and the degree of overlap between its range and that of its potential hosts. Records of both woodlouse-parasitizing flies and their hosts were obtained from two citizen science platforms: Facebook and iNaturalist. The extent of occurrence (EOO) and area of occupancy (AOO) were calculated for S. deceptoria and different woodlouse species. We assessed the advance of S. deceptoria into the city, comparing classic EOO and α-hull mode with a chi-squared test with Yates’ continuity correction. We found that S. deceptoria was widely distributed in the Metropolitan Region, with a significant expansion over time. Woodlouse species, although common in the city, are sparsely sampled and so their EOO and AOO are underestimated. Stevenia deceptoria had a medium to complete overlap in distribution with potential woodlice hosts. The rapid expansion of S. deceptoria is probably due to its native host invading the Metropolitan Region. It is therefore likely that this fly species will expand its current distribution to neighboring regions where exotic woodlouse species are present.